Postprandial Hyperglycemia as a Significant Risk Factor for Coronary Heart Disease - Al-Lehibi, Khalid I.; Al-Lehibi, Khalid I.; Hussein, Mousa Q.; Al-Hergani, Zaidan K. (AL-Kindy College Medical Journal, 2011)
Background: The highest concentrations ofblood glucose during the day are usually foundpostprandialy. Postprandial hyperglycemia (PPH)is likely to promote or aggravate fastinghyperglycemia. Evidence in recent years suggeststhat PPH may play an important role in functional& structural disturbances in different body organsparticularly the cardiovascular system.Objective: To evaluate the effect of (PPH) as arisk factor for coronary Heart disease in Type 2diabetic patients.Methods: Sixty-three type2 diabetic patientswere included in this study. All have controlledfasting blood glucose, with HbA1c correlation.They were all followed for five months period(from May to October 2008). A two hourpostprandial glucose (PPG) was done for all. Otherrisk factors were taken in consideration such ashypertension, obesity, and dyslipidemia. The studywas performed on those patients after at least threemonths of controlled fasting blood glucose. ECGwas done to all of them.Results : Out of the 63 type 2 diabetic patients,20 had normal PPG and HbA1c levels, one of them(5%), has ischemic changes on ECG twentypatients had normal HbA1c & High PPG with 7(35%) of them showed ischemic changes on ECG17 patients showed a high PPG and a high HbA1cwith four of them showed ischemic changes onECG P